Cutting-edge nanotechnology: unveiling the role of zinc oxide nanoparticles in combating deadly gastrointestinal tumors - Guo, Yonggang; Morshedi, Mohammadamin (Frontiers in Bioengineering and Biotechnology, 2025)
Zinc oxide nanoparticles (ZnO-NPs) have gained significant attention in cancer therapy due to their unique physical and chemical properties, particularly in treating gastrointestinal (GI) cancers such as gastric, colorectal, and hepatocellular carcinoma. These nanoparticles generate reactive oxygen species (ROS) upon entering cancer cells, causing oxidative stress that leads to cellular damage, DNA fragmentation, and apoptosis. ZnO-NPs affect the expression of key proteins involved in apoptosis, including p53, Bax, and Bcl-2, which regulate cell cycle arrest and programmed cell death. Additionally, ZnO-NPs can reduce mitochondrial membrane potential, further enhancing apoptosis in cancer cells. Furthermore, ZnO-NPs inhibit cancer cell proliferation by interfering with cell cycle progression. They reduce levels of cyclins and cyclin-dependent kinases (CDKs), leading to cell cycle arrest. ZnO-NPs also exhibit anti-metastatic properties by inhibiting the migration and invasion of cancer cells through modulation of signaling pathways that affect cell adhesion and cytoskeletal dynamics. The efficacy of ZnO-NPs in overcoming chemotherapy resistance has been demonstrated by their ability to reduce the IC50 values of chemotherapeutic agents, making cancer cells more susceptible to drug-induced cell death. In this review, we summarize the mechanisms by which ZnO-NPs exert anticancer effects in GI cancers, focusing on apoptosis, cell cycle regulation, and metastasis inhibition, while also highlighting the current limitations in translating these findings into effective clinical treatments.